Silver ion adsorption using alkali and organosilane modified coconut pith biosorbents - Saman, Norasikin (Taylor and Francis Ltd., 2015)
The coconut pith biosorbents were prepared by modifying coconut pith (CP) with sodium hydroxide and bis(triethoxysilylpropyl) tetrasulfide to enhance its sorption capacity and selectivity toward silver ion [Ag(I)]. It was found that the Ag(I) sorption capacity of pure CP, CP modified with sodium hydroxide, and CP modified with bis(triethoxysilylpropyl) tetrasulfide was 0.50, 0.48, and 0.62 mmol/g, respectively. The Ag(I) equilibrium data were best fitted to the Langmuir isotherm model, whereas the kinetic data obeyed the pseudo-second-order kinetic model with the anticipation of the film diffusion as the rate-limiting step. The sorption process was generally governed by a combination of physical and chemical sorption mechanisms. The Ag(I) sorption capacity and selectivity of coconut pith biosorbents were low as compared with other metal ions.